Exclusion and Reintegration in a Social Dilemma - Alice Solda; Marie Claire Villeval (Institute of Labor Economics (IZA), 2017)
Using a negatively framed public good game, we study the cooperative behavior of individuals who reintegrate their group after being excluded by their peers. We manipulate the length of exclusion and whether this length is imposed exogenously or results from a vote. We show that people are willing to exclude the least cooperators although it is not an equilibrium strategy. Exclusion has a positive impact on cooperation when it is followed by a quick rather than a slow reintegration and that the length of exclusion is chosen by the group. In this environment, a quicker reintegration also limits retaliation. Post-exclusion cooperation and forgiveness depend not only on the length of exclusion but also on the perceived intentions of others when they punish.
Keywords: C92; H41; D23; 330; ostracism; exclusion; reintegration; social dilemma; cooperation; experiment